MAHASISWA MEMBANTU PENDIDIKAN WARGA SURAKARTA DI MASA PANDEMI COVID-19 - Sholihin As’ad; Halwan Halwan; Agus Rahmadi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2020)
On 13th March 2020, the Mayor of Surakarta declared the city emergency state as a patient of Moewardi Hospital of Surakarta died due to coronavirus infectious. People have to face several restrictions and follow the health protocol in order to break the coronavirus spread. This paper presents the empowering of students of Universitas Sebelas Maret (UNS) to educate people in Surakarta during the COVID-19 pandemic through the student community service program known as Kuliah Kerja Nyata (KKN). Twenty students from various study programs and faculties of UNS organized themselves to educate and to assist the people in the area where they live. They taught and assisted children and teenagers in solving their learning problems in school and for the housewife making useful products that are needed during a pandemic. These were held both face to face and online interaction. The social and physical distancing forced the students to limit their physical interaction with others. They used online social media such as Instagram, WhatsApp, Facebook, and video conference application to support their work. The most program was conducted in a small community, such as Rukun Tetangga (RT). Well-coordinated among students, the chief of RT (Ketua RT) and the supervisor made this project successfully done.